Life cycle assessment of spectra-managed greenhouses for sustainable agriculture - Muhammad Usman Sajid (16078039) (2023)
Plants in agricultural greenhouses utilize the visible spectrum for photosynthesis, while the unused solar spectrum contributes to greenhouse temperature rise. The spectra-managed greenhouses employ innovative techniques to mitigate the cooling load by means of solar spectrum filtering. This study aims to conduct a comprehensive comparative life cycle assessment of conventional and spectra-managed greenhouses specifically designed for hot and arid climates. The novel roof greenhouse integrates photovoltaics and dielectric mirrors for solar spectrum optimization, while the nanofluid roof greenhouse uses spectrum-selective nanofluid for sustainable cooling. The life cycle assessment (LCA) evaluates the environmental impacts of greenhouse components and processes, identifying the hot spots for environmental performance improvement at the early stage of development. The life cycle impact assessment (using TRACI approach) showed that novel roof greenhouse could reduce global warming potential (GWP), acidification potential (AP), eutrophication potential (EP), smog formation potential (SFP), and fossil fuel depletion (FFD) by 52.4%, 47.7%, 49.8%, 53.2%, and 57.4%, respectively, compared to the conventional greenhouse. Electricity is a significant contributor to environmental emissions for all analyzed greenhouses; therefore, a sensitivity analysis is performed by varying the source of electricity. For photovoltaic-generated electricity to power the greenhouses, the implementation of a nanofluid roof greenhouse resulted in a 23.4% and 21.8% reduction in GWP compared to novel roof and conventional greenhouse, respectively. Other Information Published in: Cleaner Environmental Systems License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1016/j.cesys.2023.100127